Closing the loop: Establishing reverse logistics for a circular economy, a systematic review. (15th February 2023) - Mallick, Pravin Kumar; Salling, Kim Bang; Pigosso, Daniela C.A.; McAloone, Tim C.
Abstract: Reverse Logistics (RL) of end-of-use/end-of-life products has become a vital part of circular economy practices for manufacturers. However, significant quantities of resources are still landfilled instead of being recovered. With mounting pressure on businesses to address the sustainability crises (resources, climate change, waste, toxicity) on account of the take-make-dispose-based linear economy, companies today realise the importance of RL but face several barriers to implementing it, including a lack of knowledge. Although several studies have investigated different aspects of RL in various industries in different country settings, less attention has been devoted to developing a systematic and holistic approach for designing and implementing RL. To address these gaps, this paper reviews 116 scholarly articles published between 2011 and 2021 to identify attributes related to the design and implementation of RL systems. Based on a systematic literature review, a conceptual framework is presented covering the key activities, drivers and barriers, stakeholder engagement and performance management in RL. Such a framework can support companies evaluate different approaches and strategies, as well as the opportunities and challenges of designing and implementing RL and transitioning towards a Circular Economy. Graphical abstract: Image 1 Highlights: Companies often face challenges in designing & implementing Reverse Logistics (RL). This paper reviews 116 papers to synthesize the state-of-the-art in RL research. It covers activities, drivers, barriers, stakeholders, metrics and incentives in RL. It also investigates industry 4.0 and role of digital technologies in RL systems. The framework for RL helps businesses plan and implement RL for a circular economy.